EFEKTIVITAS KONSENTRASI Trichoderma sp TERHADAP (Phytopthora palmivora Butl.) PADA BUAH KAKAO (Theobroma cacao L.) - Hastuti, A. Rini; Parawansa, Ayu Kartini; Gani, Mahir S. (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2025)
This study was conducted to determine the effective concentration of Trichoderma sp. against Phytophora palmivora. This study was conducted in the disease laboratory, Department of Pests and Plant Diseases, Faculty of Agriculture, Hasanuddin University. This study was carried out from March to August 2024. The method used in this study was the Detached pod test method, namely looking at cocoa fruit that had been infected with Phytopthora palmivora fungus consisting of five treatment levels T0 (Control), T1 (giving concentration 105), T2 (giving concentration 106), T3 (giving concentration 107), T4 (giving concentration 108). The parameters observed were the area of Phytopthora palmivora fungal spots on the surface of cocoa fruit and identification of the results of cocoa fruit isolation. The results showed that the treatment with a concentration of 106 had an average area of spots with a value of 8.73 mm2, which was the lowest value compared to other treatments. Treatment with a concentration of 106 showed effective control in inhibiting the growth of Phytophora palmivora and can be considered as an alternative in disease control strategies.